2006
DOI: 10.1523/jneurosci.0573-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Endoplasmic Reticulum-Retention Motif in an Intracellular Loop of the Kainate Receptor Subunit KA2

Abstract: Neuronal kainate receptors are typically heteromeric complexes composed of GluR5-7 and KA1-2 subunits. Although GluR5-7 can exist as functional homomeric channels, the KA subunits cannot. KA2 is widely expressed in the CNS, and KA2/GluR6 heteromers are the most prevalent subunit composition in brain. Previous work has identified endoplasmic reticulum (ER)-retention motifs in the C terminus of KA2, which prevent surface expression of KA2 homomers. However, we find that, when these motifs are mutated, only a sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(72 citation statements)
references
References 23 publications
5
65
0
Order By: Relevance
“…A recent paper has shown that the replacement of the RRR ER retention motif with three alanines is sufficient for a slight release of the full-length NR1-1 subunits to the cell surface of HEK-293 cells (17), which is not in agreement with our results. A similar mechanism of ER retention employing multiple ER retention motifs has been proposed for the kainate receptor subunit KA2 (18). The phosphorylation of serine residues adjacent to the RRR ER retention motif can suppress ER retention of single transmembrane chimeric proteins containing the C terminus of the NR1-1 subunit (6,7,9).…”
Section: Discussionmentioning
confidence: 63%
“…A recent paper has shown that the replacement of the RRR ER retention motif with three alanines is sufficient for a slight release of the full-length NR1-1 subunits to the cell surface of HEK-293 cells (17), which is not in agreement with our results. A similar mechanism of ER retention employing multiple ER retention motifs has been proposed for the kainate receptor subunit KA2 (18). The phosphorylation of serine residues adjacent to the RRR ER retention motif can suppress ER retention of single transmembrane chimeric proteins containing the C terminus of the NR1-1 subunit (6,7,9).…”
Section: Discussionmentioning
confidence: 63%
“…Previous studies showed that after cotransfection of GluR6 and KA2 in heterologous systems, the amount of KA2 subunit expressed at the cell membrane surface critically depends on the GluR6:KA2 cDNA ratio (Nasu-Nishimura et al, 2006). Glutamate pulses (1 mM, 100 ms) delivered to cells transfected with GluR6 elicited current responses of large amplitude (1650 Ϯ 65 pA, at a holding potential of Ϫ40 mV; n ϭ 25) (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…GluR6 and GluR6/KA2 receptors expressed in HEK293 cells mediate currents with distinct I-V relationships Cotransfection of GluR6 and KA2 cDNAs is expected to yield a mixture of homomeric GluR6 and heteromeric GluR6/KA2 [because KA2 subunits do not form functional homomers (Herb et al, 1992;Ren et al, 2003;Nasu-Nishimura et al, 2006)]. Previous studies showed that after cotransfection of GluR6 and KA2 in heterologous systems, the amount of KA2 subunit expressed at the cell membrane surface critically depends on the GluR6:KA2 cDNA ratio (Nasu-Nishimura et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Surface Biotinylation Assays-Biotinylation assays of cell surface proteins were performed as described (17). siRNAtransfected cells were washed 3 times with ice-cold phosphate-buffered saline (PBS) containing 1 mM CaCl 2 and 0.5 mM MgCl 2 (PBS(ϩ)) and incubated with 0.25 mg/ml EZ-Link Sulfo-NHS-LC-Biotin (Pierce) in PBS(ϩ) for 20 min at 4°C with gentle agitation.…”
Section: Identification Of Px-rics-interactingmentioning
confidence: 99%